A novel microfluidic paper-based analytical device based on chemiluminescence for the determination of β-agonists in swine hair. Issue 18 (24th April 2020) - Li, Wei; Luo, Yong; Yue, Xiqing; Wu, Junrui; Wu, Rina; Qiao, Yu; Peng, Qing; Shi, Bo; Lin, Bingcheng; Chen, Xu
Abstract : β-Agonists are illegal feed additives in the feed industries of many countries, especially China. Abstract : β-Agonists are illegal feed additives in the feed industries of many countries, especially China. Here, we report a microfluidic paper-based analytical device (μPAD) coupled with the chemiluminescence (CL) method to provide the sensitive, simple and rapid quantitative detection of β-agonists in swine hair samples. In this study, we found that the β-agonists diminished the CL generated by the reaction of K3 [Fe(CN)6 ] and luminol on μPAD, which was different from that observed in the aqueous solution, and the degree of diminishment was proportional to the concentration of β-agonists. The possible mechanism was discussed as well. Also, this detection method showed a wide linear range (from 4.0 × 10 −8 to 1.0 × 10 −5 mol L −1 ) and low limit of detection (2.0 × 10 −8 mol L −1 ) with a low consumption of samples and reagents. Satisfactory recovery values (from 78% to 95%) were achieved. Therefore, our μPAD CL sensor will be favorable to develop a miniaturized instrument for the on-site analysis of β-agonists in swine hair samples.